Behavior of light elements in iron-silicate-water-sulfur system during early Earth’s evolution - Iizuka-Oku, Riko (Sci Rep, 2021)
Hydrogen (H) is considered to be one of the candidates for light elements in the Earth’s core, but the amount and timing of delivery have been unknown. We investigated the effects of sulfur (S), another candidate element in the core, on deuteration of iron (Fe) in iron–silicate–water system up to 6–12 GPa, ~ 1200 K using in situ neutron diffraction measurements. The sample initially contained saturated water (D(2)O) as Mg(OD)(2) in the ideal composition (Fe–MgSiO(3)–D(2)O) of the primitive Earth. In the existence of water and sulfur, phase transitions of Fe, dehydration of Mg(OD)(2), and formation of iron sulfide (FeS) and silicates occurred with increasing temperature. The deuterium (D) solubility (x) in iron deuterides (FeD(x)) increased with temperature and pressure, resulting in a maximum of x = 0.33(4) for the hydrous sample without S at 11.2 GPa and 1067 K. FeS was hardly deuterated until Fe deuteration had completed. The lower D concentrations in the S-containing system do not exceed the miscibility gap (x <  ~ 0.4). Both H and S can be incorporated into solid Fe and other light elements could have dissolved into molten iron hydride and/or FeS during the later process of Earth’s evolution.